PERSEPSI PENONTON TAYANGAN REALITY SHOW 86 NET TV DI PERUMAHAN GRIYA SIDOHARJO ASRI SRAGEN - Suffi Al-Amin, Muhammad Kamil; Suryo, Herning; Riyanto, Buddy (Solidaritas, 2024)
One of the programs broadcast on television is a reality show program. In Indonesia,reality shows are synonymous with television shows that present games or competitions. Almostall television stations in Indonesia have reality show programs that air almost every day. The aimof this research is to describe and analyze the perceptions of viewers of the reality show 86 at theGriya Sidoharjo Asri housing complex in Sragen. The theory used in this research is the theoryof perception from Deddy Mulyana: 2017, namely a theory consisting of sensation (stimulus),attention (attention), and interpretation. This research uses a qualitative descriptive researchmethod. Data collection techniques are carried out by interviews, observation, documentation.Meanwhile, determining research subjects used a purposive sampling technique. To analyze thedata using data analysis techniques from Miles and Huberman. The results of this research showthat 86 Net TV broadcasts were perceived positively by viewers in the Griya Sidoharjo AsriSragen housing complex. This is known from the stages of sensation starting from the frequencyof viewing, presenters from the police, various information, and the addition of backgroundsound. The source's attention is based on external factors due to the novelty of the segments ineach episode. Attention based on internal factors is the biological factor of the need forinformation about the police's daily activities in carrying out their duties and physiological factorsthat are informative and educational in nature. The informant's interpretation is that theinformation conveyed by the presenter is easy to understand because the presenter is able toconvey the information well and clearly.Keywords: Perception, Audience, Reality Show 86